INTERACTIONAL MODIFICATION LANGUAGE USED BY THE TEACHER IN ENGLISH CLASSROOM IN MTS PUI CIKASO - Elin Marlina; Dadang Solihat; Nida Amalia Asikin (Universitas Kuningan, 2021)
This research aims at knowing the types of interactional modification language used by the teacher in MTs PUI Cikaso based on Pinter’s theory (2017) and also finding out the students’ responses toward interactional modification. Qualitative research design is applied in this research. The subject of the data is an English teacher and the students of class VII B MTs PUI Cikaso. The data are collected through observation, interview, and questionnaire. During observation, the researcher uses mobile phone to record the learning process by putting the phone in the corner of the class to get clear visualization. The observation is conducted 8 times (8 meetings) where every meeting spends 40 minutes. Interview used to support the data about teacher’s opinion while using interactional modification language. Meanwhile questionnaire is used to support the student’s responses. The data are analyzed both qualitatively. The findings revealed that the teacher used 5 types of interactional modifications: 1) Repetition; 2) confirmation check; 3) comprehension check; 4) clarification request; and 5) reformulation. While for the students’ responses, it showed that the students gave correct responses, incorrect responses, and no response. However, the students admitted that interactional modification language can help them to comprehend material well. It shows that 85% of the students responded positively toward interactional modification used by the teacher. In addition, the interactional modification is being responded negatively by 15% of the students. Finally, the researcher concluded that the use of interactional modification language is needed to keep students-teacher interaction run well.Keywords: Interactional modification; student’s comprehension; student’s response